The Program Bases of the Initial Fresco Decoration of the North-Western Room in the Vladychnaia Chamber (the Сell of Archbishop Ioann) of the Novgorod Kremlin - Tsarevskaya, Tatiana Iu. (Actual Problems of Theory and History of Art, 2019)
The survived murals of the Vladychnaia Chamber despite their fragmented state can help to understand ideas and images which inspired the Novgorod archbishop Euthymius in his political and ecclesiastical activities just before the turning point in the history of Velikii Novgorod. In accordance with the structure and functions of architectural spaces of the Chamber, these frescoes arranged the ceremonial preparations for the episcopal services, organized as a solemn transition to the cathedral. Obviously, the sequence and ideological content of the fresco compositions can shed light on the purpose and meaning of the various rooms and halls of this architectural complex. The article discusses the decoration of the “Cell of ArchbishopIoann” — the room, where the archbishop, most probably, spiritually prepared for the liturgy and started the liturgical procession to the Cathedral. The image of two archangels overlying the entrance portal, testify of the sacral significance of this room, most probably the private praying chapel of archbishop. The frescoes in the niches of the east wall inside the Ioann’s Cell consist of the image of “St. Sophia the Divine Wisdom” and a fragment of the fresco depicting a complicated architectural scene. The research argues that this fragment highly likely is a part of the“Crucifixion” thematically related to the image of St. Sophia the Wisdom. Both had close affinities in their compositional structure as well as in their theological content. The iconography of the fresco “Sophia the Divine Wisdom” in the Cell represents an early type which appeared in the first decades of the 15th century and formed outside Novgorod. Thus it anticipates the iconographic variant of the famous icon that appeared in the St. Sophia Cathedral about the end of 15th century and is known as “Novgorodian”.